Detection and Adhesion Gene Profiling of Biofilm-Producing Staphylococcus aureus from Chicken Meat and Raw Milk Samples - Manikkavasagan Ilangopathy; Vijayarani Kumanan; Murugan Balaraman; Meignanalakshmi Sundaram; Eswari Soundian; Ragavendiran Venkatesan (The Indian Veterinary Journal, 2026)
The present study, aimed to investigate the presence of S. aureus (Staphylococcus aureus) in food samples (chicken meat and raw milk), as well as the biofilm-forming ability of isolates, and to characterise different adhesion genes. Out of 20 chicken meat samples, five (25%) tested positive for S. aureus. Out of 20 raw milk samples, 6 (30%) tested positive for S. aureus. Microtitre plate assay revealed that all isolates were weak to moderate biofilm producers. The isolates were characterized and confirmed to be S.aureus by PCR using 16S rRNA. The adhesion genes were detected using PCR with specific primers. Among the isolates, nuclease gene nuc (60%), coagulase gene coa (80%), agr (80%), and sdrD (80%) were detected in S.aureus isolated from chicken meat. In S.aureus isolated from milk samples nuc (66%), coa (100%), agr (50%) and sdrD (50%) genes were detected. All isolates were negative for fnpB, bap, and icaD genes. This study identified biofilm-forming S. aureus in food samples, which serves as a contaminant that contributes to food spoilage. Furthermore, they pose risks to consumer health and safety.